Novel Therapeutics for Diabetic Retinopathy and Diabetic Macular Edema: A Pathophysiologic Perspective - Bunch, Katharine L.; Abdelrahman, Ammar A.; Caldwell, Ruth B.; Caldwell, R. William (Frontiers in Physiology, 2022)
Diabetic retinopathy (DR) and diabetic macular edema (DME) are retinal complications of diabetes that can lead to loss of vision and impaired quality of life. The current gold standard therapies for treatment of DR and DME focus on advanced disease, are invasive, expensive, and can trigger adverse side-effects, necessitating the development of more effective, affordable, and accessible therapies that can target early-stage disease. The pathogenesis and pathophysiology of DR is complex and multifactorial, involving the interplay between the effects of hyperglycemia, hyperlipidemia, hypoxia, and production of reactive oxygen species (ROS) in the promotion of neurovascular dysfunction and immune cell polarization to a proinflammatory state. The pathophysiology of DR provides several therapeutic targets that have the potential to attenuate disease progression. Current novel DR and DME therapies under investigation include erythropoietin-derived peptides, inducers of antioxidant gene expression, activators of nitric oxide/cyclic GMP signaling pathways, and manipulation of arginase activity. This review aims to aid understanding of DR and DME pathophysiology and explore novel therapies that capitalize on our knowledge of these diabetic retinal complications.